Energy Characteristics of the DC Distributed Power Supply Systems - Viktor Sychenko; Valeriy Kuznetsov; Artur Rojek; Petro Hubskyi; Yevhen Kosariev (Communications - Scientific letters of the University of Zilina, 2021)
Currently the circuit technology of the DC traction power supply system cannot provide the necessary requirements for introduction of high-speed traffic. Numbers of measures and tools have been developed to improve the traction lines that no longer meet current requirements. One of the most promising means for strengthening the traction DC lines is transition to the distributed power supply of the rolling stock. In this article, a comparative analysis was carried out of energy indicators of the classic centralized power system and distributed power systems with use of one aggregate traction substation and with use of the solar generators. That comparative analysis of these systems was performed on a simulation model with the same parameters of the traction line and rolling stock.